2007
DOI: 10.1086/512615
|View full text |Cite
|
Sign up to set email alerts
|

Severe Human Lower Respiratory Tract Illness Caused by Respiratory Syncytial Virus and Influenza Virus Is Characterized by the Absence of Pulmonary Cytotoxic Lymphocyte Responses

Abstract: Severe infantile RSV and influenza virus LRTI is characterized by inadequate (rather than excessive) adaptive immune responses, robust viral replication, and apoptotic crisis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
410
3
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 374 publications
(452 citation statements)
references
References 47 publications
32
410
3
7
Order By: Relevance
“…We hypothesised that children with severe bronchiolitis had a defect in the APC-IL-15-NK cell axis that prevented the development of a competent innate response to respiratory viral infection. This might account for the paucity of NK cells in lung tissue seen at autopsy studies of children who died from severe viral bronchiolitis [32]. Lymphocyte phenotyping by flow cytometry revealed a significant drop in the relative percentage of NK cells seen in the peripheral blood among children with bronchiolitis.…”
Section: Discussionmentioning
confidence: 98%
“…We hypothesised that children with severe bronchiolitis had a defect in the APC-IL-15-NK cell axis that prevented the development of a competent innate response to respiratory viral infection. This might account for the paucity of NK cells in lung tissue seen at autopsy studies of children who died from severe viral bronchiolitis [32]. Lymphocyte phenotyping by flow cytometry revealed a significant drop in the relative percentage of NK cells seen in the peripheral blood among children with bronchiolitis.…”
Section: Discussionmentioning
confidence: 98%
“…Microscopic examination of bronchoalveolar lavage fluid and lung tissue from morbid mice revealed profound inflammation, most notable for recruitment of granulocytes and for severe pulmonary edema consistent with the clinical findings characteristic of acute respiratory distress syndrome (ARDS; Figure 4). Interestingly, severe inflammation, edema and recruitment of granulocytes have also been characterized in a recent series of RSV-diagnosed post-mortem samples evaluated by Welliver and colleagues [25]. PVM replication in situ results in local production of proinflammatory mediators, including MIP-1α, MIP-2, MCP-1 and IFNγ [24].…”
Section: Inflammatory Responses and Disease Severitymentioning
confidence: 89%
“…Reprinted with permission from Rosenberg HF et al [11]. [24]; RSV images reprinted with permission from Welliver TP et al, [25]. Wild type and IFNγR gene-deleted mice were vaccinated with live-attenuated PVM strain 15 (ATCC), heat-inactivated strain 15, or diluent alone and challenged with virulent strain J3666.…”
Section: Discussionmentioning
confidence: 99%
“…59 hRSV-mediated lung pathology in mice is not completely dissected and primary reports attributed this effect to T cells, specially CD8 C T 67,68 but in humans, it has mostly been associated with a large influx of neutrophils in the lungs of patients with bronchiolitis, as well as in fatal cases of infants. [69][70][71] It is suggested that neutrophils recruitment induced by hRSV infection promote lung damage through the generation of reactive oxygen species and extracellular traps (NETs). 72,73 Nevertheless, a recent study using experimental hRSV infection of adults in which a 65% of individuals presented inflammation symptoms, has shown that the virus replicate in the lower respiratory tract, inducing cellular infiltration of CD8 C T cells to the airways.…”
Section: Both Memory Cd4mentioning
confidence: 99%